Biowaiver Monographs for Immediate Release Solid Oral Dosage Forms: Levetiracetam. Issue 9 (6th February 2015) - Petruševska, Marija; Berglez, Sandra; Krisch, Igor; Legen, Igor; Megušar, Klara; Peternel, Luka; Abrahamsson, Bertil; Cristofoletti, Rodrigo; Groot, D.W.; Kopp, Sabine; Langguth, Peter; Mehta, Mehul; et al.
<x xml:space="preserve">Abstract</x> Literature and experimental data relevant for the decision to allow a waiver of in vivo bioequivalence (BE) testing for the approval of immediate release (IR) solid oral dosage forms containing levetiracetam are reviewed. Data on solubility and permeability suggest that levetiracetam belongs to class I of the biopharmaceutical classification system (BCS). Levetiracetam's therapeutic use, its wide therapeutic index, and its favorable pharmacokinetic properties make levetiracetam a valid candidate for the BCS‐based biowaiver approach. Further, no BE studies with levetiracetam IR formulations in which the test formulation failed to show BE with the comparator have been reported in the open literature. On the basis of the overall evidence, it appears unlikely that a BCS‐based biowaiver approach for levetiracetam IR solid oral dosage forms formulated with established excipients would expose patients to undue risks. Thus, the BCS‐based biowaiver approach procedure is recommended for IR solid oral dosage form containing levetiracetam, provided the excipients in the formulation are also present in products that have been approved in countries belonging to or associated with the International Committee on Harmonization and are used in their usual quantities, and provided the dissolution profiles of the test and reference product comply with the current requirements for BCS‐based biowaivers. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2676–2687, 2015